HUBUNGAN KARAKTERISTIK IBU MENYUSUI DENGAN PEMBERIAN MAKANAN PENDAMPING ASI PADA BAYI USIA 6-24 BULAN - Elfida, Elfida; AS, Emilda; Rahmawati, Anita (Poltekkes Kemenkes Yogyakarta, 2012)
The provision of complementary foods should be done gradually and different from the type of each feeling introducing new foods began to form thick porridge, fruit juices, fresh fruit, cream foods, and snacks the food is finally solid. Babies are among the easiest to suffer from nutritional disorders. From the SDKI data shows 30% from infants under six months of age other than breast milk given food, 18% were given breast milk and formula milk, 9% were given milk and water and 20% were given milk and juice. The provision of MP-ASl is sometimes inadequate both in terms of quantity and quality. According to the SDKI only 41, 2% of infants aged 6-23 months fed according to the suggestion that ASl, more than 3 (three) and food groups with a minimum frequency of meals. Objective: To determine the relationship characteristics of breastfeeding mothers by providing complementary foods (MP-ASl) on infants aged 6-24 months in Alue Naga Village, Kuala Syiah District, Banda Aceh City. This research is a cross-sectional approach descriptive. The population in this study were mothers who had babies aged 6-24 months that were recorded in Alue Naga Village, a total of 52 respondent. The sampling technique uses a total population, data collection is done by interviews. Test statistic using the chi-square test with SPSS 16.0 and hypothesis testing based on p-value <0.05. Test results statistics with (chi-square) show that respondents with basic education provide complementary foods approach is not recommended by as many as 24 people (82.2%) p-value of 0.001 (p <0.05), respondents who have less knowledge of providing appropriate complementary feeding is not recommended by some 19 people (73.1%) p-value of 0.012 (p <0.05), and respondents who have multigravida parity providing appropriate complementary feeding are not recommended by as many as 17 people (73, 9%) p-value of 0.218 (p> 0.218). Conclusion: There is a relationship between education level and giving complementary foods ASl, there is a relationship of knowledge with complementary feeding and there is no relationship between parity and complementary feeding of infants aged 6-24 months.